Determinants of institutional delivery in three North Indian states: Evidence from DLHS 4 - Manas P Roy (Journal of Dr. NTR University of Health Sciences, 2018)
Background and Objective: Institutional delivery (ID) is considered pivotal for ensuring maternal and neonatal health. Emphasis has been put on the same in India repeatedly with aim to reduce mortality in this vulnerable group. The aim of the study is to find out the determinants of ID in north India. Materials and Methods: Data for the ecological study were retrieved from District Level Household and Facility Survey 4 (2012-13) for 53 districts in three north Indian states, viz. Punjab, Haryana, and Himachal Pradesh. District wise proportion for ID and different demographic factors were considered along with Antenatal care service components. Regression was used to find out the determinants for higher rate of ID. Results: Overall, 80% ID has been documented in the present survey in district level. Among different variables, consumption of 100 iron folic acid (IFA) tablets and higher parity were negatively associated with higher rate of ID (coefficient = - 0.692 and - 0.573, respectively), whereas uptake of three or more ANC visits was seen to be associated with it positively (coefficient = 0.422). Conclusions: ANC visits, parity and consumption of IFA tablets are associated with higher rates of ID at district level in North India.